Effect of Celebrity Endorsement and Product Involvement on Consumers’ Response to Digital Advertising - Saket Agrawal, Anish Agarwal, Preetha Menon, Kaushik Samaddar (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to investigate the extent to which celebrity endorsers complement the functional benefits and enhance the impact of ad-response. As a brand ambassador plays an instrumental role while creating a specific image of the brand in the minds of the potential customers, it becomes imperative to fathom the implications of a celebrity endorser. The study was conducted with the help of the eye-tracking technology in which thirty six respondents were selected to go through the eye-tracking process which captured the physical aspects of the attention of the consumers when they look at a digital print advertisement. The respondents were subdivided into 2 categories using the ‘Elaboration theory model’ where half of them were primed with a context. Both these groups were again divided into 2 sub-groups where one was shown an ad with a celebrity and the other was shown ads without a celebrity in the eye-tracking experiment. The parameters that were analyzed through the study were – Time to first fixation, Heat maps, and gaze plots that helped us analyze which part of the ad the viewer saw first and which part do they spend the most time at. Tobii Studio was used for completing the analysis of the collected data. The eye-tracking results were used to determine the ad-response of all four groups and then the recall scores were put through an ANOVA function to determine if there was any significant difference in the ad-response among the four groups.